Relasi dan Legitimasi Raja Dengan Ulama dalam Sistem Pemerintahan Islam di Bone - Rahmawati Rahmawati (Universitas Islam Negeri Alauddin Makassar, 2019)
This article discusses the relationship and legitimacy of the king as the highest authority of the kingdom with the ulama in the Islamic government system in the kingdom of bone. For clarity in this study, the author uses historical and anthropological studies as